2018
DOI: 10.5582/bst.2018.01265
|View full text |Cite
|
Sign up to set email alerts
|

China issues the National Essential Medicines List (2018 edition): Background, differences from previous editions, and potential issues

Abstract: Creating a "Healthy China" has become a national strategy since the Outline for the "Healthy China 2030" Plan was issued and implemented on October 25, 2016 (3). In order to promote a "healthy China," the State Council promulgated and implemented the 13th Five-Year Plan for Hygiene and Health on December 27, 2016 Summary On October 25, 2018, the National Health Commission of China issued the National Essential Medicines List (2018 edition) [NEML (2018)]. The NEML (2018) contains 685 drugs, which consist of 417… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Our study also found that some factors regarding the perception of EMs were significantly associated with the willingness for DR. NEMP aims to reduce excessive unnecessary spending. To date, China has implemented the NEMP [56,57], and the high cost of medical services for the public has been relieved [58]. Several studies have proved that the EMs system had a positive effect in reducing both outpatient and inpatient expenses at the grassroots level [59,60], and then more patients intended to return to PMI [61].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that some factors regarding the perception of EMs were significantly associated with the willingness for DR. NEMP aims to reduce excessive unnecessary spending. To date, China has implemented the NEMP [56,57], and the high cost of medical services for the public has been relieved [58]. Several studies have proved that the EMs system had a positive effect in reducing both outpatient and inpatient expenses at the grassroots level [59,60], and then more patients intended to return to PMI [61].…”
Section: Discussionmentioning
confidence: 99%
“…As part of the commitment to giving every citizen access to basic healthcare, China implemented the National Essential Medicines Policy (NEMP), which aims to increase the availability and affordability and to ensure the quality and promote the rational use of medicines. Since the revision of the National Essential Medicines List (NEML) issued in 2009, the list has been updated constantly from 307 medicines (2009) to 520 medicines (2012) and 685 medicines (2018), for fully meeting the needs of basic healthcare 55. Based on the literature review on the evaluation of the effects of the NEMP, there is no consensus conclusion.…”
Section: Coverage Of Health Servicesmentioning
confidence: 99%
“…As the base of drug supply and security system, the national essential medicines system reform is comprehensive and includes but is not limited to the following: the selection, production and distribution of essential medicines; quality assurance; reasonable pricing; tendering and procurement; a zero mark-up policy on sales; rational use and reimbursement; and monitoring and evaluation 57. The government issued a revision of the National Essential Medicines List (NEML) in 2009 including a list of 307 essential medicines, and constantly expands the list to fully meet the needs of basic healthcare 58. These on-list medicines should be available at all primary care institutions.…”
Section: Main Reform Initiatives and Achievements Of The Past Decadementioning
confidence: 99%